Pengaruh Kemampuan Berpikir Kreatif dan Positif terhadap Prestasi Belajar Matematika - Melia Kristania (JKPM (Jurnal Kajian Pendidikan Matematika), 2016)
Double regression of corrasional survey is aimed at, 1) acknowledging the impacts of both creative thinking ability and positive thinking on mathematical learning achievement all together 2) acknowledging the impacts of students’ creative thinking ability on mathematical learning achievement 3) acknowledging the impact of students’ positive thinking on mathematical learning achievement.  The  research was conducted at SMK Assalam, Kelurahan Cisalak, Cimanggis Districts, Depok in 2015/2016 by using simple random sampling with 93 respondents taken from the number of population reach as many as 122 respondents. The instrument used is test on variables of mathematical learning achievement and questionnaire on variables o creative thinking ability and positive thinking ability and all instruments have been empirically validated. Hypothesis test was conducted after the data fulfill in series of classic assumption test, i.e. normality test, linearity test and multicollinearity test. Hypothesis test with Ftest and test. The research result show that 1) there are significant impacts of both creative thinking ability and positive thinking on mathematical learning achievement all together 2) there aresignificant impacts of students’ creative thinking ability on mathematical learning achievement 3) there are significant impact of students’ positive thinking on mathematical learning achievement.